Response to Beratan: Creating Equity through Challenging Ableism and Racism in IDEA - Peters, Susan (Disability Studies Quarterly, 2006)
This response supports the interactive notions of ableism and racism aptly deconstructed by Beratan, and extends the notions through examining the premises of distributive justice inherent in market-driven hegemonic discourses. However, deconstruction does not carry the argument far enough. Strategies and notions for reconstruction need articulation in order to offer a way forward. Lessons learned from Corey H. et. al. v Chicago Board of Education and responses to the No Child Left Behind Act (NCLB) provide instructive strategies and tactics necessary for redressing institutional inequity.